evaluate the following

Asked by sunil_0010 | 31st Oct, 2009, 08:46: PM

Expert Answer:

[(1+sinθ-cosθ)/(1+sinθ+cosθ)]2 =

(1+sinθ-cosθ)2/(1+sinθ+cosθ)2 =

(1+2sinθ+sin2θ-2cosθ-2sinθcosθ+cos2θ)/(1+2sinθ+sin2θ-2cosθ-2sinθcosθ+cos2θ) =

(1+2sinθ+1-2cosθ-2sinθcosθ)/(1+2sinθ+1+2cosθ+2sinθcosθ) = 

(2+2sinθ-2cosθ-2sinθcosθ)/(2+2sinθ+2cosθ+2sinθcosθ) =

(1+sinθ-cosθ-sinθcosθ)/(1+sinθ+cosθ+sinθcosθ) =

((1+sinθ)-cosθ(1+sinθ))/((1+sinθ)+cosθ(1+sinθ)) =

(1+sinθ)(1-cosθ)/((1+sinθ)(1+cosθ)) =

(1-cosθ)/(1+cosθ)

Regards,

Team,

TopperLearning.

 

 

 

 

 

 

 

 

 

Answered by  | 1st Nov, 2009, 11:20: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.